Minat Siswa Terhadap Pembelajaran Bola Voli Kelas 8 Pada SMPN 7 Karawang Barat - Rahmat Effendi; Evi Susianti; Rizki Aminudin (Universitas Singaperbangsa, 2020)
The study aims to determine the students’ interest in the Volleyball learning towards VIII grade of SMPN 7 Karawang in Academic 2018/2019. For answer the research problem that have been formulated, the author used a quantitative descriptive approach with survey a method. The research was conducted in junior high school to 35 respondents. The population of study was the students in VIII grade of SMPN 7 Karawang, the total of populations is 144 people. According to Suharsimi Arikunto (1998:115) if the population more than 100 people, tha sample can be 10-2-% or more. In order to be more representative of this study, the researcher took the sample by using random sample technique, each element or member of the population has the same opportunity to be elected to become a sample. Based on the results of the research and discussion that has been presented, it is concluded that the interest of VIII grade students of SMPN 7 Karawang towards volleyball learning is being considered that the highest frequency is in the moderate category with 22 people or 63% of the population. The VII grade students’ interest about learning volleyball game was categorized as the very high, it was 3 people or 9%, and very low was 3 people or 9%,. For the result, it can be categorized the level of students’ interest with the interest qualification showed the result 67,71% students interest to participate the volleyball learning.